1993
DOI: 10.1016/0735-1097(93)90258-3
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular pseudohypertrophy in cardiac tamponade: An echocardiographic study in a canine model

Abstract: Left ventricular pseudohypertrophy is a constant manifestation of cardiac tamponade in a canine model. The degree of myocardial thickening correlates with the reduction of ventricular dimensions and with the severity of hemodynamic compromise, representing a constant facet of heart remodeling in cardiac tamponade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…7 A similar effect can also be seen following compression of the cardiac ventricles due to cardiac tamponade. 8 a significant decrease in left ventricular enddiastolic diameter between the first and the second echocardiographic study, which, however, cannot be explained by significant volume depletion. In contrast, tachycardia, hypotension, and a short period of preceding fluid resuscitation suggested that marked hypovolemia was present at the time of the first echocardiogram, whereas tachycardia and hypotension had resolved when the second study (i.e., time of pseudohypertrophy) was performed.…”
Section: Discussionmentioning
confidence: 78%
“…7 A similar effect can also be seen following compression of the cardiac ventricles due to cardiac tamponade. 8 a significant decrease in left ventricular enddiastolic diameter between the first and the second echocardiographic study, which, however, cannot be explained by significant volume depletion. In contrast, tachycardia, hypotension, and a short period of preceding fluid resuscitation suggested that marked hypovolemia was present at the time of the first echocardiogram, whereas tachycardia and hypotension had resolved when the second study (i.e., time of pseudohypertrophy) was performed.…”
Section: Discussionmentioning
confidence: 78%
“…The left ventricle has a simple shape, rotationally symmetric around its long axis, its wall thickness is sufficient to be reproducibly measured in clinical practice, and changes in the dimensions of its cavity and wall can be easily appreciated. Initial observations in a small selected group of patients with cardiac tamponade [12], subsequently confirmed in an experimental canine model [13], demonstrated that cardiac tamponade is associated with pseudohypertrophy, transient left-ventricular ‘remodeling’ characterized by increased diastolic left-ventricular wall thickness, decreased left-ventricular dimensions and normal (unchanged) left-ventricular mass. However, whether this phenomenon strictly reflects cardiac compression or whether it results from changes in ventricular shape associated with intrapericardial fluid accumulation per se has not been systematically investigated in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of dynamic change of LV configuration inducing pseudohypertrophy in rapid LV unloading is attractive 13,14 . Unfortunately in the orthostatic test we use only apical window for imaging focused on LVOT gradient.…”
Section: The Selection Of Stress Test To Provoke Lvotg In Hemodialyzementioning
confidence: 99%